Myths and Misconceptions Around Reducing Carbon Embedded in Cloud Platforms - Lyu, Jialun; Wang, Jaylen; Frost, Kali; Zhang, Chaojie; Irvene, Celine; Choukse, Esha; Fonseca, Rodrigo; Bianchini, Ricardo; Kazhamiaka, Fiodar; Berger, Daniel S. (2nd Workshop on Sustainable Computer Systems (HotCarbon’23), 2023)
Major cloud providers have stated public plans to lower their carbon emissions. Historically, this has meant focusing on emissions from producing the electricity consumed by datacenters. While work and challenges remain on this avenue, research and industry are actively working on the next step of reducing carbon embedded in servers and racks. At a high level, a promising direction to reduce embodied carbon is to avoid emissions from new manufacturing, which often requires using existing components, devices, and buildings for longer. However, much of the data around carbon breakdowns and reduction opportunities remains silo-ed, leading to speculations and assumptions - both internally and externally - around the opportunities to reduce datacenter carbon intensity. We aim to clarify some of the misconceptions we have encountered.